1988
DOI: 10.1172/jci113787
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-lymphocyte clusters that form spontaneously in rheumatoid arthritis synovial effusions differ from clusters formed in human mixed leukocyte reactions.

Abstract: Lymphocytes cluster about dendritic cells (DC) spontaneously in 48 h cultures of rheumatoid arthritis synovial fluid (RA SF) mononuclear cells and in peripheral blood autologous or allogeneic mixed leukocyte reactions. In the latter case, the clusters are predominantly CD4+ T cells (T4/T8 > 5) and with time progress into blastic cells that express IL-2 (Tac) and/or transferrin (T9) receptors. In contrast, the clusters in RA SF cultures have a T4/T8 ratio of < 1 and a majority of the T8 cells coexpress the Leu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…This subset was increased in peripheral blood and synovial fluid of RA patients (12) and in vitro studies have demonstrated an association between CD8+, CD57-t lymphocytes and dendritic cells derived from RA joints (25). Recently, increasing proportions of CD3 + T cells expressing CD57 (80% of which coexpress CD8) have been related to the duration of RA disease (26).…”
mentioning
confidence: 99%
“…In earlier studies, we found that CD4-bearing lymphocytes were the predominant responder cells in an allogeneic MLR (22). Thus, the observation of significant increases in the proportion of CD8 cells in the responder population that was stimulated with RA SF dendritic cells was unanticipated.…”
Section: Discussionmentioning
confidence: 78%
“…These defects are subtle, and sometimes smaller doses of the stimulatory ligands, such as mitogens or anti-CD3 antibody, are required to show the extent of the deficit (35). Many explanations have been offered for this defect, including an unequal distribution of T cell subsets in the RA cells, as opposed to normal cells (36,37), a greater number of RA T cells in the preactivated or memory state (22), or the effects of macrophagederived soluble inhibitors (35).…”
Section: Discussionmentioning
confidence: 99%